Bipolar Androgen Therapy in the management of prostate cancer - Niedobylski, Sylwiusz; Laszczak, Katarzyna; Warchoł, Konrad; Moqbil, Sara; Kalicka, Karolina (Journal of Education, Health and Sport, 2021)
Introduction and purpose: Prostate cancer (PCa) as one of the most frequent neoplasms in men remains a challenge for oncologists. The main strategy of its treatment is the Androgen Deprivation Therapy (ADT) the principle of which is an inducement of hypogonadism. The lack of testosterone is not only a factor greatly contributing to a decrease of quality of life overall, but additionally it increases the odds of the complications, including low libido and erectile disfunction, metabolic abnormalities, high cardiovascular risk, osteoporosis, anaemia, or depression. ADT also has the potential of inducement of castration resistance (CRPC), which significantly worsen patients prognosis. The main purpose of this review is to explore the Bipolar Androgen Therapy (BAT), which has the potential to solve the aforementioned problems. State of knowledge: The mechanism of BAT action has been described. BAT is effective not only against CRPC, but androgen-dependant PCa as well. BAT reverses the hormone resistance in CRPC, thus allowing the rechallenging of the ADT. It has the direct cytotoxic effect on cancer cells. Additionally BTA increases the exponents of the general quality of life of the patients. There is a number of active clinical trials regarding BAT. Conclusions: BAT is a safe therapeutic strategy with the high efficacy in reversing hormone resistance in CRPC patients, thus significantly increasing their health prognoses and it allows to alleviate or avoid the adverse effects of ADT.